Those Who Can Pay: The Impact of Socioeconomic Status in Long Term Care - Desiree Schippers (Crossing Borders: A Multidisciplinary Journal of Undergraduate Scholarship, 2020)
In this personal essay I explore the disparities between two different state funded long term care facilities. After completing four months of field work living in a nursing home, I synthesize my experiences both as a long term care resident and employee into a work of creative nonfiction. I include information from interviews with experts on long term care funding, finance officers at the facilities, and refer to state long term care laws.
Keywords: long term care; nursing home